2008
DOI: 10.1590/s1678-58782008000100011
|View full text |Cite
|
Sign up to set email alerts
|

Influence of machining parameters on fatigue endurance limit of AISI 4140 steel

Abstract: (or up-and-down) method to determine the fatigue limit of the specimens.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 25 publications
1
1
0
1
Order By: Relevance
“…Increasing the turning feed could produce a more compressive residual stress state, thus offsetting its deleterious in uence on surface roughness (stress concentration) and leading to a similar number of cycles under fatigue. This behavior was described by Lopes et al [22], who reported the same fatigue limit after turning AISI 4140 steel with two distinct feeds (0.12 and 0.18 mm/rev).…”
Section: Number Of Cycles To Failuresupporting
confidence: 80%
“…Increasing the turning feed could produce a more compressive residual stress state, thus offsetting its deleterious in uence on surface roughness (stress concentration) and leading to a similar number of cycles under fatigue. This behavior was described by Lopes et al [22], who reported the same fatigue limit after turning AISI 4140 steel with two distinct feeds (0.12 and 0.18 mm/rev).…”
Section: Number Of Cycles To Failuresupporting
confidence: 80%
“…This effect decreases with an increase in temperature due to the relaxation of residual stress. Lopes et al [6] also stated that the fatigue limit of AISI 4140 steel decreases with increasing roughness parameters.…”
Section: Introductionmentioning
confidence: 95%
“…Los efectos de los parámetros de corte (velocidad de corte, avance y profundidad de corte) durante el maquinado están muy bien documentados y un gran número de estudios se han realizado para estudiar los efectos de la rugosidad producida por el maquinado en el rendimiento de piezas mecá-nicas sometidas a fatiga [15], [14]. La capa superficial se somete a deformación elasto-plástica, calentamiento (que resulta en cambios estructurales), endurecimiento por deformación y estreses residuales [16]. De la Tabla 1 obtenemos los valores de potencia y torque del vehículo y de la Figura 13 las dimensiones de la sección fallada.…”
Section: A Modelo Teórico De Esfuerzosunclassified